Preparation and properties of novel polydimethylsiloxane composites using polyvinylsilsesquioxanes as reinforcing agent. (January 2015) - Chen, Dongzhi; Hu, Xiaoyun; Zhang, Hongwei; Yin, Xianze; Zhou, Yingshan
Abstract: A series of novel polydimethylsiloxane (PDMS) composites were prepared using polyvinylsilsesquioxanes (PVS) as reinforcing agent by hydrolytic condensation in the presence of organotin catalyst for the first time. The cross-linked network, morphology, thermal behavior and mechanical properties of these novel PDMS composites were examined by attenuated total reflection infrared spectroscopy (ATR-IR), scanning electron microscope (SEM), thermogravimetric analysis (TGA) and universal tensile testing machine, respectively. Experimental results showed that both thermal and mechanical properties of the PDMS composites were improved greatly by adding PVS. The prominent improvements in thermal and mechanical properties were likely attributed to the reinforcing interaction of PDMS chains and formed particles resulted from PVS self-crosslink. Meanwhile, we also found that with the increment in loading PVS, the resistance to thermal degradation of the PDMS composites in nitrogen atmosphere was enhanced obviously, but their resistance to thermal oxidation in air was not improved apparently. The unobvious improvement in resistance to thermal oxidation of the novel composites was likely due to the catalysis of oxygen.